مقاصد الشریعة وأثرھا في تنزیل الأحكام الفقھیة على الوقائع - نماذج مختارة - - صیاد, الحادة (University of Eloued-جامعة الوادي, 2016)
This research studies: the purposes of Sharia and its impact on the application of jurisprudential provisions on the facts, as it combined theoretical rooting for the subject; it was about the reality of the purposes of Sharia and the application of jurisprudential provisions on the facts, and some of it's contemporary applications. In conclusion, the research reached some results and recommendations, including that the purposes is guiding the provision of Sharia on the facts during it's application. And other results attached and detailed in the folds of the search.
مذكرة ماستر
Keywords: مقاصد الشريعة/الاحكام الفقهية/الواقائع; Objectives of Sharia/Fiqh rulings/Facts